CervixCheck: A Spiritually-Based Text Messaging Intervention to Promote Cervical Cancer Awareness and Pap Test Screening Intention among African-American Women. Issue 9 (2nd September 2018) - Le, Daisy; Holt, Cheryl L.
Abstract : Background/Purpose: On a national level, African-American women have a 34% higher incidence of cervical cancer and are twice as likely to die of the disease when compared to White women. In response to the need to improve cervical cancer prevention and Pap test screening knowledge and utilization, we developed and pilot tested a 16-day SMS text message-based intervention. The CervixCheck study was designed to develop, pilot test, and evaluate the feasibility, acceptability, and initial efficacy of a spiritually-based SMS text messaging intervention aimed at increasing cervical cancer awareness and Pap test screening intention in church-attending African-American women ages 21–65. Methods/Approach: The Theory of Planned Behavior guided the development of the CervixCheck intervention. This intervention utilized a non-experimental one-group pretest-posttest design. In this article, we present findings from the pilot testing phase. Of the 52 participants at baseline, 46 completed the post-program survey. Results/Findings: The current study provides evidence for the early feasibility, high acceptability, and some initial efficacy of the CervixCheck intervention. There was a significant pre-post increase observed for knowledge about cervical cancer and the Pap test (p = .001) and subjective norms (p = .006). Findings post-intervention also revealed that 83% of participants reported being either "satisfied" or "very satisfied" with the CervixCheck intervention and 85% found the SMS text messages either "useful" or "very useful". Conclusions/Significance: A spiritually-based SMS text messaging intervention could be a culturally-appropriate and cost-effective method of promoting cervical cancer early detection information to church-attending African-American women.